Frontiers in celiac disease - Fasano, Alessio; Troncone, Riccardo; Branski, D (Karger, 2008)
Few other fields in human biology have experienced such a tremendous progress as celiac disease has during the past few years. The contributors to \'Frontiers in Celiac Disease\' are world-renowned opinion leaders who made these advances possible. Their expertise has been assembled here to provide a comprehensive overview of the current knowledge of the epidemiology, pathogenesis, clinical presentations, diagnosis and treatment of celiac disease. In addition, the stage is set for innovative strategies for preventive interventions and treatment alternatives to a gluten-free diet. A valuable reference for basic and translational scientists, this book also serves as a practical resource to healthcare professionals, including general practitioners, subspecialists, dieticians, nutritionists, and nurses and nurse practitioners. Students from different disciplines will find this book a helpful guide to expand and deepen their knowledge of celiac disease.
Pediatric and adolescent medicine, ISSN 1017-5989 vol. 12
Keywords: celiakie; Allergy and Immunology; Celiac Disease; alergologie a imunologie